Diachronic and Cultural Variations in Chukchi Ethnobotany - Belichenko, Olga; Kolosova, Valeria; Jernigan, Kevin; Pupynina, Maria (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2021)
Although the ethnoecology of the Chukchi has long been the focus of researchers, a systemic description informing the history of plant use, including local names or modes of harvesting and preparation, suitability for different ages, and different occasions, is largely lacking. C. H. Merck provided the first account of food plants at the end of the 18th century, during the Billings-Sarychev expedition, however, the first information regarding traditionally used medicinal plants was published only recently, after centuries of contact. During our 2014-2015 fieldwork, we interviewed 56 Chukchi people in the Chukotskii and Iultinskii districts of Chukotka to collect material on the most common local plants. We also gathered data on Chukchi ethnobotany from all available published sources. Slight differences were observed between maritime and reindeer Chukchi, with the former relying more on plant resources. Access limitations (e.g., algae) are reduced by exchanges between the two groups. The decline in the consumption of roots gathered from vole nests (peɬqumret) is compensated by an increase in berry harvesting (e.g., cloudberry, crowberry, bog blueberry, and lingonberry). Our results also show that the main medical uses are aimed at disease prevention, though some are borrowed from scientific pan-Russian herbal medicine popularized during the Soviet period.